ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI VOLUME PENJUALAN PRODUK OLAHAN KENTANG “FRENCH FRIED” - Syarif Imam Hidayat (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2008)
“French Fried” is one of potato agrifood product by PT Siantar Top Tbk Sidoarjo. Nowadays it sales indicate decreasing than many years ago. Because many competitors that produce a lot of same agrifood product in market. So, producer must create market strategy to maintain customer and how to make customer satisfaction. The research aimed to analyze some factors it impact in sales volume. The analyze method that used in this research is multiple regression analyze. The result shows that a number of product, price, and distribution channells are significantly effect to sales volume either in partial or simultaneously. As recommended to producers to push and more intensive to performance some factros as result effectively and continously. The result indicate that alternative strategy it means how a firm to maximize strenghts variables in obtaining opportunities market with possible ways are implied. Key words : French Fried, Potato, sales volume